Mapping the landscape of Islamic fintech and financial inclusion: a bibliometric review - Muhamad Dupi; Muhammad Adil (Journal of Islamic Accounting and Finance Research, 2026)
Purpose - This study aims to systematically map and analyze the global research landscape on Islamic fintech and financial inclusion, identifying key publication trends, leading contributors, collaborative networks, and dominant research themes during from 2015 to 2026. Method - This study employed bibliometric analysis using data extracted from the Scopus database. A total of 1,428 English-language journal articles were analyzed using the PRISMA approach. Bibliometric techniques, including author collaboration analysis, citation collaboration analysis, and co-occurrence of keywords, were performed using VOSviewer (version 1.6.20) for visualization. Result - The findings indicate significant growth in research output, particularly during the 2022–2025 period. China and India lead in productivity, while the United Kingdom and the United States demonstrate a strong research impact. The literature has evolved into a multidimensional field, integrating financial technology with sustainability and inclusive development. Implication - This study makes a theoretical contribution by mapping the intellectual framework of research on Islamic fintech and offers practical insights for strengthening regulations and promoting financial inclusion. Originality - This study presents a recent bibliometric analysis of Islamic fintech and financial inclusion, offering a comprehensive overview of the field’s developments and research trends.